Compact non-astigmatic alexandrite ring laser with unidirectional single-longitudinal-mode operation - Sathian,J; Tawy,G; Sheng,X; Minassian,A; Damzen,MJ (2019)
Progress in single frequency and precise wavelength tunable lasers are essential to address future demands in high resolution spectroscopy, metrology and quantum technology systems. Alexandrite lasers with wide tunability in near-IR spectral region when pumped by low cost red diodes provide a good prospect as a cost effective precision laser source. This was demonstrated in our earlier work [1] using a tunable single-frequency bow-tie cavity with Brewster-cut Alexandrite crystal. The astigmatism of the Brewster cut gain medium and need for angled curved mirrors for astigmatic compensation, whilst being well established [2,3] also places some complexity on the design and can be compromised by astigmatic thermal lensing [1]. Here we report the investigation and successful operation of a non-astigmatic compact design of a unidirectional wavelength tunable Alexandrite ring laser with single frequency operation.